PERANCANGAN ALAT PIROLISIS LIMBAH PLASTIK MENJADI BAHAN BAKAR MINYAK - Rachmadianty, Alya; Sopiyan, Sopiyan; Luby, Ahmad (LPPM, Universitas Negeri Jakarta, 2023)
The scarcity of fuel oil energy has led to the development of research on additional and alternative energy sources for fuel. one of the alternatives that can be utilised from the large amount of plastic waste scattered in the environment becomes environmental pollution. Is the processing of plastic waste so that it can be processed into fuel oil solutions. Tools for processing plastic waste into fuel oil using the pyrolysis process. Further research is needed regarding the design of pyrolysis equipment. This research uses computational methods by testing on computer devices using CAE software, namely Solidwork, inventor and Ansys and then testing also uses experimental methods and computational 3-dimensional analysis to obtain a suitable design to produce pyrolysis compressors which include thermal and structural testing. The pyrolysis device of waste plastic into fuel oil has the highest temperature at the combustion surface of 500.47 ℃ and the temperature is stable at 143.95 ℃. the temperature inside the plastic combustion reactor is at 489.23 ℃. the cooling water temperature of 24 ℃ can LMTD value of 83.6 ℃. raw material of 10 kg LDPE produces liquid smoke from the weight of plastic which is 7.04 kg with a volume of 6.56 litres in one process. Dimensional strength and tool strength are used in the design of pyrolysis equipment with materials including stainless steel 304 and 316 then monel and copper can experience a maximum total heat flux change of 12.261 W/mm2 and has a safety factor value of 15. from Plastic waste can be processed and utilised into fuel oil. One type of plastic that can be utilised is LDPE waste using the pyrolysis process using appropriate calculations in the study.